Halodoc Adoption Model: Integration of UTAUT2, Perceived Risk, and Trust with PLS-SEM - Dian Putrawangsa; Audria Ineswari Mulya Marhadi; Hedie Kristiawan; Adi Anggoro Parulian; Thomas Gilbert Alvintra; Avelya Minaka Putri (STMIK Widya Cipta Dharma, 2025)
The development of digital health technology, also known as healthtech, has transformed the opportunities and ways people access healthcare, particularly through telemedicine. In Indonesia, Halodoc has become one of the most widely used telemedicine platforms, offering easy access and affordable online healthcare services. Despite its various conveniences, user adoption remains inconsistent due to persistent issues and public perceptions regarding perceived risk and lack of trust in online consultation methods. This study aims to develop a model for Halodoc adoption by developing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) with perceived risk and trust in medical personnel. Using a quantitative approach, data responses were collected from online Halodoc users through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) techniques with the help of SmartPLS. The results show that only facilitating conditions, habit, and price value have a significant influence on behavioral intention to adopt Halodoc. Extensive factors suspected of influencing Halodoc adoption, namely perceived risk and trust in medical personnel, did not have a significant influence, especially in the Indonesian context. The results of this study add to the role and benefits of UTAUT2 in the healthcare context, especially in Indonesia, with managerial implications for enhancing the role of facilitating conditions, habits, and price value in order to increase the adoption of Halodoc and other digital healthcare in Indonesia.